Determining the equivalence degree on the basis of lexical field “elevation” / Einige Überlegungen zur Bestimmung des Äquivalenzgrades am Beispiel des lexikalischen Feldes „Erhebung im Gelände“ - Katinas, Daumantas (Kalbotyra, 2015)
The equivalence of ration of lexical units in two languages, which are compared, is still not answered definitely in the fields of lexicology, lexicography and translation studies. Most lexicologists, comparing two or more languages, distinguish full or partial match or the absence of equivalence. However, there is only partial match between the lexemes in two languages in practice. Therefore, a mathematical formula is proposed to calculate the equivalence ratio of the lexemes in two languages. Firstly, this article outlines semantic analysis of “elevation” in Lithuanian and German languages. Secondly, a mathematical approach is proposed to calculate the equivalence of two tokens, which are compared. In the last part of the article, the same mathematical formula is used to analyze kalva ʻhillʼ and Hügel ʻhillʼ. Then the summary and conclusions are provided. Abstract in German